A new hexagonal porous carbon nanoplate material derived from Al-based metal organic framework for high performance supercapacitors. (1st March 2021) - Liu, Xingyu; Wang, Pingyuan; Chang, Cuiping; Chen, Yongmei; Sun, Yanzhi; Tang, Yang; Wan, Pingyu; Pan, Junqing
Highlights: A new hexagonal porous carbon nanoplate (HPCN) was prepared via a green and non-template pathway. HPCN delivers a hierarchical porous structure and large specific surface area (2123 m 2 g −1 ). The particle size of HPCN could be adjusted by changing the initial metal ion concentration. HPCN-0.1 exhibits high specific capacitance of 297 F g −1 at 1 A g −1 and excellent cyclic stability. Abstract: In recent years, the application of metal organic frameworks and their derivatives has become more and more wide and frequent in the field of electrochemistry. Herein, a hexagonal porous carbon nanoplate (HPCN) material was prepared using Al-based metal organic framework (Al-BTC) through a simple one-step carbonization and KOH washing method. The obtained HPCN displays uniform nanostructure of hexagonal nanoplate, with an enormous BET surface area (2123 m 2 g −1 ) and suitable average pore size (1.9 nm). The HPCN product shows 297 F g −1 at 1 A g −1 and 317.4 F g −1 at 1 mV s −1 through electrochemical test of a three-electrode system. It also has excellent stability with 94.6% capacitance retention at a high current density of 50 A g −1 over 200000 cycles. In addition, electrochemical tests conducted in a two-electrode system shows that the specific capacitance is as large as 57.3 F g −1 at 1 A g −1 and the power density reaches 13.5 Wh kg −1 at 635.8 W kg −1 . Besides, the particle size of Al-BTC and HPCN could be adjusted by changing the initial metal ion concentration, which would greatly affect the specific surface area and electrochemical performance of HPCN. This study will provide a new strategy for the preparation of carbon electrode materials with high performance. Graphical abstract: Image, graphical abstract